DETERMINASI KINERJA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - YOLANDA WIJAYA; NELLIYANA NELLIYANA (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study is to obtain the empirical evidence about determinants of the performance of non-financial companies. Independent variables used in this study are board meetings, attendance of the board members, board size, leverage, firm age, firm size, sales growth and liquidity. Population of this study is non-financial companies listed on Indonesia Stock Exchange from 2014-2016. There are 331 samples selected using purposive sampling method. Hypothesis testing method used in this study is multiple regression linear. The results of this study shows that two independent variables are board meetings and board size have influence to the firm performance. While the other six independent variables are attendance of the board members, leverage, firm age, firm size, sales growth and liquidity have no influence to the firm performance.